Web-Based Information System for Listing Goods at the Semoga Jaya Store - Ramadhan, Ade Prasetyo; Asroni, Asroni; Kurnianti, Aprilia (Universitas Muhammadiyah Yogyakarta, 2021)
Manual processing at the Semoga Jaya Store troubles the owner. This issue necessitates an information system that the business owner and customers can access immediately, at any time, and from any location. The system must offer precise, fast, and accurate information on the available stock. Hence, this study created a web-based information system designed with the Hypertext Processor (PHP) programming language and the MySQL database. The system could ease the store’s financial data management, offer information on its stock, and facilitate customers to discover information on the goods. This research involved needs analysis, system design, implementation, and testing. Functional testing was conducted on this stock list information system, revealing that it could facilitate data processing and provide information effectively and efficiently.